Solid electrolyte, lithium battery adopting solid electrolyte and preparation method of lithium battery

By using polymer monomers containing unsaturated bonds in lithium batteries, and using them in conjunction with the composite liquid collector to form an electronic insulating layer, the problem of thermal runaway in the needle puncture test of lithium batteries is solved and the battery is improved Safety and energy density.

CN119133592APending Publication Date: 2024-12-13WANXIANG 123 CO LTD

Patent Information

Application Number
CN202411268508.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing lithium batteries have thermal runaway problems in needle puncture testing, and the existing composite fluid improvement methods cannot effectively reduce the occurrence of internal short circuits, resulting in insufficient battery safety.

Method used

Solid electrolytes are prepared by polymer monomers and nitrile monomers containing unsaturated bonds, and used in conjunction with the composite fluid collection to form an electronic insulating layer during needle puncture to reduce the occurrence of short circuits and thermal runaway.

Benefits of technology

Through the synergistic action of solid electrolytes and composite fluid collectors, the risk of short-circuiting of lithium batteries during needle puncture is significantly reduced, the safety of battery abuse is improved, and the quality and cost of battery are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133592A_ABST
    Figure CN119133592A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium battery technology, in particular to a solid electrolyte, a lithium battery adopting the solid electrolyte and a preparation method of the lithium battery. The lithium battery comprises a positive plate containing a composite current collector, a negative plate, a diaphragm, a package and a solid electrolyte, the negative plate, the diaphragm and the positive plate are sequentially laminated in the packaging layer, and the solid electrolyte is filled among the negative plate, the diaphragm and the positive plate; the solid electrolyte and the composite current collector have an unexpected synergistic effect in the aspect of improving safety, in a needling experiment, when the solid electrolyte and the composite current collector are used at the same time, a relatively complete electronic insulating layer can be formed on the needling surface when the battery is penetrated by a needling needle, and occurrence of short circuit and thermal runaway is reduced; by using the composite current collector, the mass of the current collector in the battery is reduced, and the reduction of the battery capacity caused by high impedance of the solid electrolyte and the composite current collector is compensated, so that the sacrifice of the energy density of the battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to lithium battery technology, and in particular to a solid electrolyte, a lithium battery using the solid electrolyte and a preparation method thereof. Background Art

[0002] The safety issue of high-energy-density lithium batteries is the main obstacle to their commercialization as power batteries. Among them, the needle penetration test can simulate the situation when an electric vehicle encounters an accident and foreign objects pierce the battery and induce a battery short circuit. It is an important characterization method to verify the safety of lithium batteries. The thermal runaway of the battery in the needle penetration test can be divided into the following steps: the steel needle simulating the foreign object pierces the separator and the positive and negative electrodes of the battery, causing a local internal short circuit; the chemical energy stored in the battery is converted into thermal energy, causing the contact part to heat up rapidly, dissolving the surrounding separator, and inducing a larger-scale battery internal short circuit; the large-scale internal short circuit leads to further heating, prompting the positive electrode material to release oxygen, the combustion of the electrolyte and the negative electrode, and finally causing a comprehensive thermal runaway.

[0003] Currently, a mainstream technical solution to improve the safety of needle puncture is to use a composite current collector with a metal / polymer / metal structure instead of a conventional metal current collector. The polymer material has a higher fracture strength than the metal ductility. When the needle penetrates the battery, the polymer layer is stretched and wrapped around the needle, reducing the contact area between the needle and the electrode, increasing the battery impedance, and reducing the short-circuit current, thereby suppressing the occurrence of thermal runaway.

[0004] However, the main characteristics of existing high-energy-density lithium batteries are: 1. The main materials of the positive and negative electrodes (high-nickel ternary, silicon + carbon materials) have high electronic conductivity and extremely low internal resistance; 2. The stored electrochemical energy density is high. Therefore, when acupuncture causes a local internal short circuit in the battery, even if there is a very small contact area between the needle and the electrode, the instantaneous temperature of the punctured area can exceed the melting temperature of the diaphragm (~120°C), causing a comprehensive thermal runaway of the battery. In the puncture experiment, the conventional metal / polymer / metal composite current collector cannot effectively reduce the occurrence of internal short circuits. It can usually only partially wrap the needle, reduce the short-circuit current size and the heating rate, which has limited effect on the suppression of internal short circuits.

[0005] In order to reduce the short circuit risk of the battery during acupuncture, CN213459794U adds two layers of high temperature resistant insulating glue on the outside of the composite current collector structure, and CN217239544U adds an insulating layer between the metal and polymer layers, thereby reducing the short circuit risk during acupuncture. However, the above improved methods for composite current collectors increase the complexity and cost of current collector preparation, and increase the mass and impedance of the current collector, thereby reducing the energy density of the lithium battery. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a solid electrolyte, a lithium battery using the solid electrolyte and a preparation method thereof. The lithium battery using the composite current collector can reduce short circuits when punctured by a needle when fully charged, fundamentally reduce the occurrence of thermal runaway, and improve the abuse safety of the battery.

[0007] Technical solution:

[0008] In a first aspect, the present application provides a solid electrolyte:

[0009] A solid electrolyte comprises a polymer monomer, a solvent, an additive for preventing further decomposition of an electrolyte, a lithium salt and an initiator; the polymer monomer contains an unsaturated bond, the polymer monomer, the lithium salt, the solvent, the additive and the initiator are mixed to obtain a precursor solution, and the precursor solution is subjected to an in-situ polymerization reaction to prepare a solid electrolyte.

[0010] Furthermore, the mass ratio of the polymer monomer, the solvent, the additive and the lithium salt is 5-20:62.5-77.5:5:12.5; and the initiator is 0.5wt% of the mass of the polymer monomer.

[0011] Furthermore, the polymer monomer includes a cross-linking monomer having a double bond number greater than or equal to 2 in its structure.

[0012] Furthermore, the polymer monomers include ester monomers containing unsaturated bonds and nitrile monomers containing unsaturated bonds.

[0013] Furthermore, the ester monomer containing an unsaturated bond is one or more of polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, ethylene glycol diacrylate, polycaprolactone dimethacrylate, tripropylene glycol diacrylate, α,ω-dimethacrylate-based polyethylene glycol, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, diallyl isocyanurate, triallyl isocyanurate, and tris(2-acryloyloxyethyl)isocyanurate; the nitrile monomer containing an unsaturated bond is one or more of acrylonitrile, allyl cyanide, 4-pentenenitrile, 5-hexenenitrile, 2-butenenitrile, trans-butenenitrile, and cinnamononitrile.

[0014] Ester monomers containing unsaturated bonds and nitrile monomers containing unsaturated bonds are used in the polymer monomers. The polymer of the ester monomers containing unsaturated bonds has high tensile strength, bending strength and compression strength, and can better wrap the punctured objects; nitrile monomers containing unsaturated bonds with high polarity, heat resistance and weather resistance are used in the polymer monomers, and are matched with ester monomers containing unsaturated bonds, which can improve the heat resistance of the solid electrolyte and inhibit the main material of electronic conductivity from moving to the puncture needle to cause a short circuit when puncture occurs, thereby reducing the occurrence of internal short circuits.

[0015] Furthermore, the mass ratio of the ester monomer containing an unsaturated bond, the nitrile monomer containing an unsaturated bond, the solvent, the additive, and the lithium salt is 5 / 0.5-0.75 / 76.75-77.25 / 5 / 12.5; and the mass fraction of the initiator is 0.5% of the polymer monomer.

[0016] Further, the solvent includes one or more liquid solvents commonly used in the field of lithium ion batteries, such as ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, succinonitrile, ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, propyl propionate, etc. The present invention does not limit the type, content and ratio of the solvent.

[0017] Furthermore, the additives include one or more additives commonly used in the field of lithium-ion batteries, such as fluoroethylene carbonate, vinylene carbonate, ethylene sulfite, 1,3-propane sultone, etc.: the present invention does not limit the type, content and proportion of the additives.

[0018] Furthermore, the lithium salt includes one or more salts commonly used in the field of lithium ion batteries, such as lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), etc. The present invention does not limit the type, content and ratio of the salt.

[0019] In a second aspect, the present application provides a lithium battery with a solid electrolyte:

[0020] A solid electrolyte lithium battery comprises a positive electrode sheet, a negative electrode sheet, a diaphragm, a packaging layer and a solid electrolyte; the diaphragm is located between the packaging layer and the negative electrode sheet, and between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and the negative electrode sheet are arranged alternately, and the two sides close to the packaging layer are negative electrode sheets; the solid electrolyte is filled between the negative electrode sheet, the diaphragm and the positive electrode sheet.

[0021] Furthermore, the diaphragm has a structure of ceramic layer / base membrane layer / ceramic layer, the thickness of the ceramic layer is 1-5μm, and the thickness of the base membrane layer is 7-10μm; the raw material of the ceramic layer includes one or more of aluminum hydroxide, aluminum oxide, titanium oxide, boehmite, and lithium aluminum titanium phosphate; the raw material of the base membrane layer includes one of polyethylene, polypropylene, polyethylene / polypropylene composite, polyester, polyamide, and aramid.

[0022] The technical effect of the diaphragm is that it acts as an electronic insulating material to isolate the positive electrode and the negative electrode inside the battery, and provides a space for the solid electrolyte, thereby achieving electronic insulation and ion conductivity between the positive and negative electrodes.

[0023] In a third aspect, the present application provides a method for preparing a lithium battery with a solid electrolyte:

[0024] A method for preparing a solid electrolyte lithium battery, comprising the following preparation method:

[0025] Preparation of dry battery cell: stacking the negative electrode sheet, the separator and the positive electrode sheet in sequence to prepare a dry battery cell;

[0026] Preparation of lithium battery: Inject solid electrolyte precursor into dry battery cell, solidify, attach packaging layer to prepare lithium battery.

[0027] Further, the negative electrode sheet preparation process is as follows:

[0028] Dispersing the negative electrode active material, conductive agent and binder in water to prepare a uniformly dispersed negative electrode slurry, coating the negative electrode slurry on the front and back sides of the copper foil in sequence, baking, rolling, slitting and punching to obtain a negative electrode sheet;

[0029] The positive electrode active material, conductive agent and binder are dispersed in an appropriate amount of N-methylpyrrolidone to prepare a uniformly dispersed positive electrode slurry, and the positive electrode slurry is coated on the front and back sides of the composite current collector, and the positive electrode sheet is obtained through baking, rolling, slitting and punching; the composite current collector has a three-layer structure of Al layer / polymer layer / Al layer.

[0030] Furthermore, the thickness of the single-sided Al layer is 0.1-2 μm, and the thickness of the polymer layer is 3-10 μm.

[0031] Furthermore, the polymer includes polymers commonly used in composite current collectors, such as PET, PI, PP, PVDF, PVDF-HFP, PEO, and PF.

[0032] The solid electrolyte and the composite current collector work synergistically to form an insulating layer on the surface of the needle in the needle penetration test, reducing the occurrence of internal short circuits. In normal battery use, it replaces the traditional electrolyte and plays the role of conducting lithium ions.

[0033] The composite current collector replaces the inner metal layer with a polymer with lower density and higher tensile strength, thereby improving the overall energy density and abuse safety of the battery.

[0034] In the preparation of the battery, the injected traditional electrolyte is replaced with a solid electrolyte precursor, and then a solid electrolyte is generated by in-situ polymerization, and the traditional metal Al foil is replaced with a composite current collector. The present invention finds that the solid electrolyte and the composite current collector have an unexpected synergistic effect in improving safety. In the needle puncture experiment, the solid electrolyte and the composite current collector are used at the same time. When the battery is pierced by the needle, a relatively complete electronic insulation layer can be formed on the needle puncture surface, reducing the occurrence of short circuit and thermal runaway. The reasons for the above beneficial effects are: first, because the solid electrolyte fully fills the internal pores of the diaphragm in the lithium battery, the thickness is consistent with the thickness of the diaphragm; second, it fully fills the gap between the positive electrode and the diaphragm, and the gap between the negative electrode and the diaphragm, and forms a continuous and uniform interface layer at the contact surface of the positive electrode material layer / diaphragm and the negative electrode material layer / diaphragm; third, the solid electrolyte fully fills the inside of the positive electrode material layer and the negative electrode material layer in the lithium battery, and exists in the gap between the active material, the binder and the conductive agent, forming a continuous ion conductive network, and the thickness of the ion conductive network is consistent with the thickness of the positive electrode material layer or the negative electrode material layer. Therefore, when the polymer foil in the positive electrode composite current collector is driven by the puncture needle and undergoes plastic deformation, the diaphragm can achieve stronger adhesion to the positive electrode main material through the solid electrolyte, inhibiting the main material with electronic conductivity from moving toward the puncture needle to trigger a short circuit, thereby reducing the occurrence of internal short circuit.

[0035] Beneficial effects:

[0036] The invention provides a lithium battery, which comprises an in-situ polymerized solid electrolyte and a composite current collector of an Al / polymer / Al foil structure.

[0037] By replacing the injected traditional electrolyte with a solid electrolyte precursor during battery preparation, generating a solid electrolyte by in-situ polymerization, and replacing the traditional metal Al foil with a composite current collector, the present invention discovered an unexpected synergistic effect of the solid electrolyte and the composite current collector in improving safety. In the puncture experiment, the solid electrolyte and the composite current collector were used at the same time. When the battery was penetrated by the puncture needle, a relatively complete electronic insulation layer could be formed on the punctured surface, reducing the occurrence of short circuits and thermal runaway.

[0038] In terms of cost, the synergy of the composite current collector and the solid electrolyte can be achieved through solid electrolyte precursor injection, heating and curing, and battery formation. The preparation process is fully compatible with conventional liquid batteries, and high safety can be achieved without any additional processing of the existing composite current collector.

[0039] In terms of performance, the use of composite current collectors reduces the mass of the current collectors in the battery. The solid electrolyte does not increase the extra thickness and mass of the battery, but instead reduces the amount of electrolyte held by the battery after it is manufactured. Both reduce the final mass of the battery at the same time, compensating for the decrease in battery capacity caused by the high impedance of the solid electrolyte and composite current collector, thereby reducing the sacrifice in battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 , is a schematic structural diagram of a lithium battery according to Example 1 of the present invention;

[0041] Figure 2 , are the temperature and voltage change curves of the puncture site of the lithium battery of Example 3 of the present invention before and after puncture;

[0042] Figure 3 , are the temperature and voltage change curves of the puncture site of the lithium battery of Comparative Example 1 of the present invention before and after puncture;

[0043] Figure 4 , is the temperature and voltage change curve of the puncture site of the lithium battery of Comparative Example 2 of the present invention before and after puncture;

[0044] Figure 5 , are the temperature and voltage change curves of the puncture site of the lithium battery of Comparative Example 3 of the present invention before and after puncture;

[0045] Figure 6 , are the temperature and voltage change curves of the puncture site of the lithium battery of Comparative Example 4 of the present invention before and after puncture.

[0046] Figure numerals: 1, positive electrode sheet; 2, negative electrode sheet; 3, separator; 4, packaging layer; 5, solid electrolyte; 11, positive electrode material; 12, composite current collector; 21, negative electrode material; 22, copper foil; 121, Al layer; 122, polymer layer. DETAILED DESCRIPTION

[0047] In order to make the technical solution of the present invention clearer, the present invention is further described in detail with reference to the following embodiments and drawings.

[0048] Example 1

[0049] A lithium battery, the structural diagram of which is as follows Figure 1 , and its preparation method comprises the following preparation steps:

[0050] Preparation of negative electrode sheet 2: Disperse the negative electrode active material (graphite), conductive agent (carbon black), and binder (styrene-butadiene rubber + sodium carboxymethyl cellulose, mass ratio 1:1) in water at a mass ratio of 97:1:2, and prepare a uniformly dispersed negative electrode slurry according to the pulping process. Coat the negative electrode slurry on the front and back of the copper foil, bake, roll, cut, and punch to obtain a negative electrode sheet 2 (including negative electrode material 21 and copper foil 22).

[0051] Preparation of positive electrode sheet 1: The positive electrode active material (LiNi0.8Co0.1Mn0.1O2), conductive agent (carbon black), and binder (polyvinylidene fluoride) are dispersed in an appropriate amount of N-methylpyrrolidone at a mass ratio of 96:2:2, and a uniformly dispersed positive electrode slurry is prepared according to the pulping process. The positive electrode slurry is coated on the front and back surfaces of the composite current collector (the composite current collector is an Al layer / PET layer / Al layer structure, the thickness of the Al layer is 0.7μm, and the PET layer is a polymer layer) with a thickness of 6μm, and the positive electrode sheet 1 (including the positive electrode material 11, the Al layer 121 and the PET layer 122) is obtained after baking, rolling, slitting, and punching.

[0052] Preparation of dry battery pack: positive electrode sheet 1, negative electrode sheet 2, separator 3 with a thickness of 15 μm, separator-(negative electrode-separator-positive electrode-separator) n - negative electrode-diaphragm structure, the sheets are stacked in sequence to prepare a dry battery cell group, and in this embodiment, n=24.

[0053] The separator 3 has a boehmite / polyethylene / boehmite structure.

[0054] Preparation of precursor solution:

[0055] The moisture content in the glove box is controlled to be no more than 10 ppm, ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate are stirred and mixed in a mass ratio of 30 / 5 / 45 / 20, and the solvent is obtained by purification and removal of impurities and water with a molecular sieve.

[0056] In a glove box, neutral alumina is used to remove the inhibitor of pentaerythritol tetraacrylate monomer, and the mixture is mixed with solvent, fluoroethylene carbonate and lithium hexafluorophosphate in a mass ratio of 5 / 77.5 / 5 / 12.5, and 0.5% azobisisobutyronitrile by mass fraction of the monomer is added as an initiator. After stirring until clarified, a precursor solution of solid electrolyte 5 can be obtained.

[0057] Preparation of lithium battery: In a protective atmosphere with a moisture and oxygen content of no more than 10 ppm, a precursor solution of solid electrolyte 5 is injected into a dry battery cell group. After curing at 38°C, the precursor solution is solidified into solid electrolyte 5. Then, a packaging layer 4 is attached to the outer surface of the battery cell group to prepare a lithium battery with a designed capacity of approximately 36 Ah.

[0058] Embodiment 2:

[0059] A lithium battery, compared with Example 1, is different in that the mass ratio of pentaerythritol tetraacrylate, acrylonitrile, solvent, fluoroethylene carbonate, and lithium hexafluorophosphate in the precursor solution is 5 / 0.25 / 77.25 / 5 / 12.5.

[0060] Embodiment 3:

[0061] A lithium battery, compared with Example 1, is different in that the mass ratio of pentaerythritol tetraacrylate, acrylonitrile, solvent, fluoroethylene carbonate, and lithium hexafluorophosphate in the precursor solution is 5 / 0.5 / 77 / 5 / 12.5.

[0062] Embodiment 4:

[0063] A lithium battery, compared with Example 1, is different in that the mass ratio of pentaerythritol tetraacrylate, acrylonitrile, solvent, fluoroethylene carbonate, and lithium hexafluorophosphate in the precursor solution is 5 / 0.75 / 76.75 / 5 / 12.5.

[0064] Embodiment 5:

[0065] A lithium battery, compared with Example 1, is different in that the mass ratio of methyl methacrylate, solvent, fluoroethylene carbonate, and lithium hexafluorophosphate in the precursor solution is 20 / 62.5 / 5 / 12.5.

[0066] Comparative Example 1:

[0067] A lithium battery, compared with Example 3, the difference is that the electrolyte is a mixture of solvent, fluoroethylene carbonate and lithium hexafluorophosphate in a mass ratio of 82.5 / 5 / 12.5, and does not contain polymer monomers and azobisisobutyronitrile.

[0068] Comparative Example 2:

[0069] A lithium battery, compared with Example 3, is different in that the positive electrode slurry is coated on an Al foil with a thickness of 12 μm.

[0070] Comparative Example 3:

[0071] A lithium battery, compared with Comparative Example 3, is different in that the positive electrode slurry is coated on an Al foil with a thickness of 12 μm.

[0072] Comparative Example 4:

[0073] A lithium battery, compared with comparative example 2, is different in that the solvent components of the electrolyte include ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and ethoxypentafluorocyclophosphazene, which are mixed in a mass ratio of 30 / 5 / 38 / 20 / 7.

[0074] Performance testing:

[0075] The electrochemical performance and safety performance of the lithium battery of the present invention are illustrated below by using data from examples and comparative examples.

[0076] Experiment 1: Electrical performance of lithium batteries

[0077] The following steps are used in the examples and comparative examples of this patent for manufacturing and data collection: at 25°C, the battery is charged to 4.25V at 0.1C constant current and constant voltage, the cut-off current is set to 0.05C, and then discharged to 2.8V at 0.1C constant current to obtain a 0.1C constant capacity Q 0.1C (Ah); then charged to 4.25V at 0.3C constant current and constant voltage, the cut-off current was set to 0.05C, and then discharged to 2.8V at 0.3C constant current, and the 0.3C constant capacity Q was obtained. 0.3C (Ah) and discharge energy E (Wh); weigh the mass of the battery after manufacture M (g). Mass energy density W = E / M*1000 (Wh / Kg), and the relevant test results are shown in Table 1.

[0078] Table 1. Summary of experimental data on the electrical performance of lithium batteries in various embodiments and comparative examples

[0079] distinguish <![CDATA[Q 0.1C (Ah)]]> <![CDATA[Q 0.3C (Ah)]]> E(Wh) M(g) W(Wh / Kg) Example 1 34 32.95 119.24 463.83 257.08 Example 2 35.2 34.6 126.08 459.49 274.39 Example 3 35.55 34.82 126.85 460.48 275.47 Example 4 35.15 34.47 125.58 460.44 272.7 Example 5 33.91 30.76 111.42 466.77 238.7 Comparative Example 1 36.26 35.6 130.09 465.5 279.45 Comparative Example 2 35.64 34.79 126.05 468.67 268.96 Comparative Example 3 36.91 36.38 133.05 478.3 278.18

[0080] By comparing Example 1 with Example 5, it can be seen that the solid-state battery prepared using a cross-linked monomer with multiple double bonds has a higher capacity than a conventional single-double bond monomer. This is because the cross-linked monomer can be polymerized to generate a polymer cross-linked network with strong solid-liquid ability, so the monomer ratio required to achieve electrolyte solidification is lower. By comparing Examples 1 to 4, it can be seen that when the content of the cross-linked monomer is fixed, the introduction of a small amount of strong polar monomers can improve the capacity of the solid-state battery, but too high a content of the strong polar monomer will also lead to a decrease in the battery capacity.

[0081] By comparing Comparative Example 1 with Comparative Example 3, it can be seen that in the liquid battery system, the use of PET foil instead of Al foil increases the battery internal resistance and reduces the discharge energy, but also reduces the overall battery mass by reducing the foil mass, compensating for the loss of battery mass energy density; By comparing Example 3 with Comparative Example 2, it can be seen that in the solid-state battery system, through appropriate polymer component design, the use of PET foil instead of Al foil does not affect the discharge energy, but also reduces the battery mass, resulting in an increase in energy density; By comparing Comparative Example 2 with Comparative Example 3, it can be seen that under the same foil condition, due to the lower ionic conductivity of the solid electrolyte, the solid-state battery has a higher internal resistance than the liquid battery, but also reduces the free electrolyte content in the solid-state battery; By comparing Example 3 with Comparative Example 2, it can be seen that on the basis of the solid-state battery, the Al foil is replaced by PET foil, which further reduces the battery mass. Under the synergistic effect of the PET foil and the solid electrolyte, the energy density of the solid-state battery is not significantly reduced compared to the traditional liquid battery.

[0082] Experiment 2: Battery cell component ignition experiment

[0083] The batteries of Comparative Example 2 and Comparative Example 4 were disassembled at 100% SOC, and the solid electrolyte, the diaphragm filled with the solid electrolyte, the positive electrode sheet, and the negative electrode sheet were collected respectively. An attempt was made to ignite them with an open flame in an air atmosphere. The relevant test results are shown in Table 2.

[0084] Table 2. Ignition test results of each component of the lithium battery of Comparative Example 2 and Comparative Example 4

[0085] distinguish Comparative Example 2 Comparative Example 4 Electrolytes Instant Burning non-flammable Electrolyte-Separator Composite Instant shrinkage and burning Shrinks instantly and continues to burn in contact with open flames Positive electrode non-flammable non-flammable Negative plate Instant Burning Instant Burning

[0086] Comparing Comparative Example 2 with Comparative Example 4, it can be seen that in a lithium battery without flame retardant ingredients, except for the positive electrode sheet of the stabilized oxide main material, the electrolyte, the diaphragm, and the negative electrode sheet will all burn when exposed to open flames. Although the addition of flame retardant ethoxy pentafluorocyclophosphazene can ensure that the solid electrolyte itself is non-flammable, it occupies a low proportion in the pores in the diaphragm or the negative electrode sheet, and cannot prevent the diaphragm and the negative electrode sheet from being ignited. In addition, the diaphragm containing the flame retardant solid electrolyte will also experience severe thermal shrinkage at high temperatures, so in the needle puncture test, it induces a larger area short circuit, causing the battery to thermally run away due to self-discharge.

[0087] Experiment 3: Puncture test of lithium battery

[0088] The embodiments and comparative examples of this patent adopt the following steps to conduct the needle penetration test: the battery is clamped in a clamping plate, and charged to 4.25V at 0.3C constant voltage and constant current under 10PSI pressure, and the cut-off current is set to 0.05C, and then a stainless steel needle with a diameter of 3mm is used at a speed of 80mm / s at 25°C to penetrate the entire battery from the direction perpendicular to the battery cell pole piece. After penetration, the steel needle is left inside the battery cell for one hour, or it can be removed after the battery cell temperature drops below 50°C.

[0089] Figure 2 , Figure 3 , Figure 4 and Figure 5 The temperature and voltage change curves of the puncture site of the lithium batteries of Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 before and after puncture are shown in order. The time when all punctures occur corresponds to the 10th second of the x-axis coordinate in the figure.

[0090] Table 3. List of puncture test data of lithium batteries of Examples 1 to 6 and Comparative Examples 1 to 4

[0091] distinguish Whether through acupuncture Maximum temperature of needle puncture Voltage before acupuncture Voltage 60s after acupuncture Example 3 yes 28.3℃ 4.210V 4.209V Comparative Example 1 no 384.1℃ 4.183V 0V Comparative Example 2 no 1038℃ 4.120V 0V Comparative Example 3 no 476.8℃ 4.204V 0V Comparative Example 4 no 568.5℃ 4.203V 0V

[0092] As shown in Table 2, in all the puncture tests, only the battery of Example 3 did not experience thermal runaway. Figure 2 The temperature and voltage changes of the puncture site before and after the stainless steel needle penetrated each battery are shown. There was no internal short circuit in Example 3, so the temperature of the battery core did not change due to the penetration of the steel needle. Comparative Examples 1 to 4 all had internal short circuits quickly after the steel needle penetrated, and the temperature of the puncture site rose to above 350°C, far exceeding the dissolution temperature of the diaphragm (120°C), and exceeded the phase transition temperature (135°C) from the layered phase to the spinel phase when the eight-series ternary positive electrode is fully charged. This transition is accompanied by the release of oxygen, which acts as a combustion aid, leading to the combustion of the electrolyte and the negative electrode material. Comparing the puncture results of the batteries in Comparative Examples 1 to 3, it can be seen that in the liquid battery system, using PET foil instead of Al foil, or in the Al foil system, replacing the electrolyte with a solid electrolyte, is not enough to prevent the dissolution of the diaphragm and the release of oxygen at the positive electrode, and therefore cannot prevent the battery from entering irreversible thermal runaway. By observing the puncture results of Example 4, it can be seen that once an internal short circuit occurs, even if the electrolyte components are made non-flammable, it is impossible to suppress thermal runaway of the battery. The above conclusions prove the advantage of the current collector and solid electrolyte in synergistically suppressing short circuits, thereby improving the safety of battery puncture.

[0093] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A solid electrolyte, It is characterized in that It includes polymer monomers, solvents, additives for preventing further decomposition of electrolyte, lithium salts and initiators; the polymer monomers contain unsaturated bonds, the polymer monomers, lithium salts, solvents, additives and initiators are mixed to obtain a precursor solution, and the precursor solution is subjected to an in-situ polymerization reaction to prepare a solid electrolyte.

2. The solid electrolyte according to claim 1, It is characterized in that The mass ratio of the polymer monomer, solvent, additive and lithium salt is 5-20:62.5-77.5:5:12.5; the mass fraction of the initiator is 0.5% of the polymer monomer.

3. The solid electrolyte according to claim 1, It is characterized in that The polymer monomers include ester monomers containing unsaturated bonds and nitrile monomers containing unsaturated bonds.

4. The solid electrolyte according to claim 3, It is characterized in that The ester monomer containing an unsaturated bond is one or more of polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, ethylene glycol diacrylate, polycaprolactone dimethacrylate, tripropylene glycol diacrylate, α,ω-dimethacrylate-based polyethylene glycol, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, diallyl isocyanurate, triallyl isocyanurate, and tris(2-acryloyloxyethyl)isocyanurate; the nitrile monomer containing an unsaturated bond is one or more of acrylonitrile, allyl cyanide, 4-pentenenitrile, 5-hexenenitrile, 2-butenenitrile, trans-butenenitrile, and cinnamononitrile.

5. The solid electrolyte according to claim 3, It is characterized in that The mass ratio of the ester monomer containing unsaturated bonds, the nitrile monomer containing unsaturated bonds, the solvent, the additive and the lithium salt is 5 / 0.5-0.75 / 76.75-77.25 / 5 / 12.5; the initiator is 0.5wt% of the mass of the polymer monomer.

6. A lithium battery using the solid electrolyte according to any one of claims 1 to 5, It is characterized in that It includes a positive electrode sheet, a negative electrode sheet, a separator, a packaging layer and a solid electrolyte; the separator is located between the packaging layer and the negative electrode sheet, and between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and the negative electrode sheet are arranged alternately, and the two sides close to the packaging layer are negative electrode sheets; the solid electrolyte is filled between the negative electrode sheet, the separator and the positive electrode sheet.

7. A lithium battery according to claim 6, It is characterized in that The diaphragm has a structure of ceramic layer / base film layer / ceramic layer, the thickness of the ceramic layer is 1-5μm, and the thickness of the base film layer is 7-10μm; the raw material of the ceramic layer includes one or more of aluminum hydroxide, aluminum oxide, titanium oxide, boehmite, and lithium aluminum titanium phosphate; the raw material of the base film layer includes one of polyethylene, polypropylene, polyethylene / polypropylene composite, polyester, polyamide, and aramid.

8. A method for preparing the lithium battery according to any one of claims 6 to 7, It is characterized in that The invention comprises the following preparation method: Preparation of dry battery cell: the separator, negative electrode sheet and positive electrode sheet are connected in the form of separator-(negative electrode-separator-positive electrode-separator) n - negative electrode-diaphragm structure, stacking the sheets in sequence to prepare a dry battery cell group, where n≥1; Preparation of lithium battery: inject solid electrolyte precursor into dry battery group, solidify, attach packaging layer, and prepare lithium battery.

9. The method for preparing a lithium battery according to claim 8, It is characterized in that The preparation process of the negative electrode sheet is as follows: Dispersing the negative electrode active material, conductive agent and binder in water to prepare a uniformly dispersed negative electrode slurry, coating the negative electrode slurry on the front and back sides of the copper foil in sequence, and then baking, rolling, slitting and punching to obtain a negative electrode sheet; The preparation process of the positive electrode sheet is as follows: The positive electrode active material, conductive agent and binder are dispersed in an appropriate amount of N-methylpyrrolidone to prepare a uniformly dispersed positive electrode slurry, and the positive electrode slurry is coated on the front and back sides of the composite current collector, and the positive electrode sheet is obtained through baking, rolling, slitting and punching; the composite current collector has a three-layer structure of Al layer / polymer layer / Al layer.

10. The method for preparing a lithium battery according to claim 9, It is characterized in that The thickness of the Al layer is 0.1-2 μm, and the thickness of the polymer layer is 3-10 μm.

Citation Information

Patent Citations

  • Method for preparing gel diaphragm cell by in-situ polymerization and prepared battery

    CN103258977A

  • Solid metal lithium battery and preparation method thereof

    CN110048153A

  • Solid-state battery and preparation method thereof

    CN114156432A

  • In-situ cured polymer electrolyte, preparation method thereof and lithium ion battery

    CN114221021A

  • Porous composite foil, positive pole piece, negative pole piece, semi-solid lithium ion battery and preparation method

    CN115832195A

Cited By

  • Manganese-based lithium battery, preparation method thereof and power utilization device comprising manganese-based lithium battery

    CN120545363A

  • Positive pole piece as well as preparation method and application thereof

    CN120878738A

  • A positive electrode sheet, a method for manufacturing the same, and use thereof

    CN120878738B

  • Battery device and electric device

    WO2026143554A1